COMPUTER SIMULATOR GAME IN YOUTH CULTURE - Elizaveta M. Kudryashova; Ekaterina M. Lyubimtseva; Vera M. Yushchenko; Sof’ya G. Barinova (Russian Studies in Culture and Society)
Purpose. The purpose of the study is to determine the place, meaning, perspectives of the computer game simulator “The Sims” in the cultural space of youth, supplemented by a new digital environment, and to establish the reasons for its 20-year success.